The use of e-mail communication with the family physician: Fourteen month's experience - Granja, Mónica (2009)
Objectives: To evaluate message exchange, between a family physician and her patients, during the first fourteen months of e-mail access. Study Design: Observational cross-sectional. Setting: A family practice in Senhora da Hora, Matosinhos, Portugal. Population: E-mail messages exchanged between physician and patients. Methods: A random sample of 20% of patient messages was evaluated for: person the message was written about, size, number and type of subjects mentioned, whether or not it elicited a reply from the family physician and, if so, the reply message size and time between initial message and reply, time of day messages were sent and message results. Socio-demographic and familiar data were collected for every patient using e-mail.The amount of time spent by family physician adressing e-mail during a whole week was measured. For descriptive statistical analysis the author used Excel 2003. Results: A total of 504 messages were received from 92 different patients, whose mean age was 37.1, being 73% of which female and 65% with higher education. The family physician herself sent 462 messages. Messages studied (n = 100) from patients were written about 112 persons (most often the one who wrote the message, children, dependent elderly or spouse). Mean message size was 57.1 words and mentioned a mean of 1.3 subjects (most often medical questions, test results, nursing or administrative procedures and medication). The family physician replied to 69% of the messages received, doing so in less than 48 hours for 94.2% of cases and using a mean of 58.2 words per message. Messages from patients were written out of hours in 22% of cases.The family physician sent 58% of replies during non-consultation time. Most often, the messages results were: reply with medical information or advice, prescription fills, tests or treatment forms, certificates, appointment scheduling and referral. During a week, the family physician took an average of 5 minutes and 31 seconds daily to address e-mail. Conclusions: As in other studies conducted in the United States, this study found that patients and carers, mainly professionally active and higher educated female, adhere to e-mail to communicate with their family physician, without causing physician overload. These results may favour higher adherence of family physicians to e-mail and of family practices to invest in this tool.